Level of Public Satisfaction with Sports Facilities at Medan State University Stadium - Silwan, Argubi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2026)
This study aims to determine the level of public satisfaction with the sports facilities at the Medan State University Stadium. The study used a quantitative descriptive approach involving 30 respondents, consisting of students and the general public who use the stadium facilities. The research instrument was a closed-ended questionnaire using a Likert scale covering indicators of facility and infrastructure conditions, cleanliness, security, comfort, accessibility, and facility management. Data were analyzed using Statistical Package for the Social Sciences (SPSS)to obtain percentage values, average (mean), and satisfaction level categories. The results of the analysis show that the level of public satisfaction is in the category Good with an overall average score of 3.87 (scale 1–5) or 77.4%. The aspects of cleanliness (mean = 4.02) and security (mean = 3.95) obtained the highest scores, while the aspect of completeness and maintenance of facilities (mean = 3.65) obtained the lowest score. These findings indicate that in general, the stadium sports facilities have met user expectations, although improvements are still needed in the aspects of maintenance and completeness of facilities to optimally improve service quality.